Faktor Risiko Yang Berhubungan Dengan Kejadian Dermatitis Di Wilayah Kerja Puskesmas Bajo Barat Kabupaten Luwu - Arif, Muh. Ikbal; Juherah, Juherah; Aspa, Nabila Nur Annisa (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
Dermatitis is an environment-based skin disease of a subjective clinical symptomatic nature of inflammation of the skin. Pay attention to environmental conditions and personal hygiene to reduce risk factors for transmission and environment-based disease rates. The purpose of the study was to determine the relationship between risk factors and the incidence of dermatitis in the work area of UPT PKM Bajo Barat, Luwu Regency. The research method is analytical observation using a case control approach. The total sample size was 134 samples consisting of 67 case samples and 67 control samples. The research sample used a random sample system using a statistical chi square test. The results of the study found a significant relationship with a history of skin disease (p = 0.000, OR = 3.0, CI 95% = 2.326-4.114), temperature (p = 0.000 OR = 2.3, CI 95% = 1.624-3.475), humidity (p = 0.000 OR=2.1, CI 95%=1.526-2.980), personal hygiene (p = 0.033 OR= 1.5, CI 95%= 993-2.169) with the incidence of dermatitis and while there was no significant mororation between the physical quality of water (p = 0.0116 OR=575,  CI 95%=288-1,149) with the incidence of dermatitis in the work area of UPT Puskesmas Bajo Barat, Luwu Regency. The conclusion of the research results of subjective dermatitis complaints is influenced by a history of skin diseases, temperature, humidity and poor personal hygiene, so it is recommended that the UPT PKM Bajo Barat can conduct counseling to the public about the importance of controlling and the harmful effects of dermatitis skin disease and the community is expected to be able to maintain their own health and hygiene and pay attention to the conditions of the living environment